INTERNATIONAL LEGAL ASPECTS OF THE DIPLOMATIC PROTOCOL - A. A. Nagieva; F. Sh. Larina (Московский журнал международного права, 2018)
INTRODUCTION. The article examines the legal nature of the norms of the diplomatic protocol and ceremonial, based on the usages of international law, on the terms of international agreements and on acts of national legislation, in particular on the legislation of the Russian Federation. Special attention is focused on the application practice of the diplomatic protocol’s and ceremonial’s rules, as well as the consequences of violation of these norms for bilateral and multilateral diplomacy. Separately it is worth noting the historical review of the formation and development of the norms of the diplomatic protocol and ceremonial, both in Europe, in general, and in the Russian Empire, later in the Soviet period and the current trends in the development of protocol norms in the Russian Federation. MATERIALS AND METHODS. The materials for the study were the works of leading Russian and foreign professionals in the field of international law and diplomacy. In preparing this article, the works of not only contemporary authors in this sphere, but also classics, whose works have not lost their relevance for he purposes of this article, were taken into account. The methodological basis of scientific research was made up of general and special methods of cognition (dialectical method, method of analysis and synthesis, deduction and induction, comparative legal and historical method). RESEARCH RESULTS. Based on the results of the study, the article analyzes in detail historical aspects of the formation and development of the norms of the diplomatic protocol and ceremonial. The contents of the norms of the national legislation of the Russian Federation are set forth, which fix certain norms of the diplomatic protocol and ceremonial. Special attention should be paid to the numerous historical examples set forth in the article, which clearly demonstrate the consequences of violation of the norms of the diplomatic protocol and ceremonial for bilateral and multilateral diplomatic relations. DISCUSSION AND CONCLUSIONS. In the article the authors come to the conclusion that the significance of the norms of the diplomatic protocol and ceremonial for bilateral and multilateral diplomatic relations is increasing, which is due to the increase in international relations between states and between states and international organizations. Significant contribution to the development of the norms of the diplomatic protocol and ceremonial is made by acts of national legislation.